2011
DOI: 10.1007/s00294-011-0362-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic transformation of Diaporthe phaseolorum, an endophytic fungus found in mangrove forests, mediated by Agrobacterium tumefaciens

Abstract: We describe the genetic transformation of the mycelial tissue of Diaporthe phaseolorum, an endophytic fungus isolated from the mangrove species Laguncularia racemosa, using Agrobacterium tumefaciens-mediated transformation (ATMT). ATMT uses both the hygromycin B resistant (hph) gene and green fluorescent protein as the selection agents. The T-DNA integration into the fungal genome was assessed by both PCR and Southern blotting. All transformants examined were mitotically stable. An analysis of the T-DNA flanki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 83 publications
1
16
0
Order By: Relevance
“…Although many of the species included in study are well known as pathogens of important crops, the extensive sampling from various geographic locations and different hosts has revealed that D. longicolla and D. sojae can be endophytic in tropical trees and mangroves (Cheng et al 2008;Sebastianes et al 2012;R€ onsberg et al 2013). The closely related taxa D. endophytica, Diaporthe schini, and Diaporthe terebinthifolii were originally described from Schinus in Brazil as endophytes (Gomes et al 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Although many of the species included in study are well known as pathogens of important crops, the extensive sampling from various geographic locations and different hosts has revealed that D. longicolla and D. sojae can be endophytic in tropical trees and mangroves (Cheng et al 2008;Sebastianes et al 2012;R€ onsberg et al 2013). The closely related taxa D. endophytica, Diaporthe schini, and Diaporthe terebinthifolii were originally described from Schinus in Brazil as endophytes (Gomes et al 2013).…”
Section: Discussionmentioning
confidence: 98%
“…Being one of the most dominant endophytes, Diaporthe ( Phomopsis ) species are commonly isolated as endophytes from different dicot plant hosts (Suryanarayanan et al 2002; Sun et al 2011). Some species of Diaporthe , however, show either pathogenic or mutualistic interactions with plants depending on the host and its health; for example, D. phaseolorum is pathogenic to soybean (Santos et al 2011), but endophytic in mangroves (Sebastianes et al 2011). Diaporthe spp.…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, some species of Diaporthe can be either pathogenic or harmless endophytes depending on the host and its health. For example, D. phaseolorum is pathogenic to soybean (Santos et al 2011), but endophytic in mangroves ( Laguncularia racemosa ) (Sebastiane et al 2011). With the deletion of Art.…”
Section: Introductionmentioning
confidence: 99%